2018
DOI: 10.2147/ppa.s176067
|View full text |Cite
|
Sign up to set email alerts
|

Patients' preferences in periodontal disease treatment elicited alongside an IQWiG benefit assessment: a feasibility study

Abstract: Background and purposeThe German Institute for Quality and Efficiency in Health Care (IQWiG) previously tested two preference elicitation methods in pilot projects and regarded them as generally feasible for prioritizing outcome-specific results of benefit assessment. The present study aimed to investigate the feasibility of completing a discrete choice experiment (DCE) within 3 months and to determine the relative importance of attributes of periodontal disease and its treatment.Patients and methodsThis prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…Two studies were multinational. DCEs were employed for preference elicitation in six studies,15,1720,23 two studies used TTO,12,21 one reported a DCE with WTP,24 and one study used both TTO and DCE 22. Sample sizes ranged from 182 to 1,482 participants, and all studies included adults with T2DM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies were multinational. DCEs were employed for preference elicitation in six studies,15,1720,23 two studies used TTO,12,21 one reported a DCE with WTP,24 and one study used both TTO and DCE 22. Sample sizes ranged from 182 to 1,482 participants, and all studies included adults with T2DM.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies used a TTO approach 12,21,22. In the earliest of these, patients with T2DM were presented with a pair of product profiles representing liraglutide once daily and exenatide twice daily 22.…”
Section: Resultsmentioning
confidence: 99%
“…It has been estimated that it takes from 6 months to 2 years to conduct a PP study, with recruitment of patients taking particularly longer than predicted (3). Guidelines should consider developing timeframes for conducting PP studies (11). Some have suggested that 3 months is an ample window of time to dedicate to PP study for decision-making inclusion and that time constraints should not be the driver as to whether systematic integration of PPs in regulatory decision making occurs (11).…”
Section: Obstacles In Incorporation and Assessment Of Ppsmentioning
confidence: 99%
“…Guidelines should consider developing timeframes for conducting PP studies (11). Some have suggested that 3 months is an ample window of time to dedicate to PP study for decision-making inclusion and that time constraints should not be the driver as to whether systematic integration of PPs in regulatory decision making occurs (11). It is also not clear when in the decision-making processes of either BRAs or HTAs PP elicitation and PP studies should be conducted and submitted (3).…”
Section: Obstacles In Incorporation and Assessment Of Ppsmentioning
confidence: 99%
See 1 more Smart Citation